The Effect of Operating Cash Flow And Book Value On Financial Distress - Ramadhan Isya Mahendra; Pujiono (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2023)
Competition in every company at this time is required to manage the business well and do new things in order to compete to maintain its business continuity. Companies that lose competitiveness will lose money and can experience financial distress. The research aims to analyze the impact of operating cash flow and book value on financial distress in state-owned companies listed on the IDX for the period 2009-2019. The research sample is a state-owned company that publishes financial statements in the 2009-2019 period in a row. The research uses a quantitative approach with a causal method. Multiple regression with SPSS was used in data analysis. The results of the study concluded that operating cash flow partially had a significant impact on financial distress. Book Value partially has insignificant impact on Financial Distress.